Clinical application of TEG (thromboelastograph) in obstetric patients. (18th April 2012) - Richmond, AK; Mitra, A; Mousa, T; Singhal, T; Dhillon, J
Abstract : Background: Thromboelastograph (TEG) has been recently introduced into obstetric care so that coagulation failure can be promptly treated. It is useful in massive obstetric haemorrhage (MOH) and DIC secondary to pre-eclampsia or sepsis. The University Hospitals of Leicester (UHL) follow an algorithm for the prescription of blood products based on TEG result. The RCOG or UHL currently do not include use of TEG in their guideline for massive obstetric haemorrhage or PPH. Methods: 10 patient case notes were reviewed from January 2010 to December 2010. The notes were selected randomly from those known to have had a TEG. We evaluated whether the TEG result influenced the blood products given to the patient. Results: Of the 10 case notes analysed, the majority had TEG investigation performed because of massive obstetric haemorrhage and two because of suspected DIC secondary to pre-eclampsia. In all cases, TEG helped identify those who needed rapid transfusion of blood products and aided further definitive management. TEG result was only abnormal in blood loss of >2500mls. The TEG algorithm was followed in 50% of abnormal results. Documentation regarding the use of TEG was consistently poor. Conclusions: TEG is an invaluable investigation in PPH, especially in patients with blood loss >2500mls or DIC. The clinical condition of the patient remains central and explains why occasionally blood products were not given despite abnormal TEG. We aim to implement guidelines for the use of TEG in PPH >1500mls and a sticker for the patient notes to aid better documentation.